Twardzina ograniczona pęcherzowa - przedstawienie dwóch przypadków, trudności terapeutyczne - Dorota Krasowska; Aldona Pietrzak; Bartłomiej Wawrzycki; Joanna Gładysz; Grażyna Chodorowska; Katarzyna Kozłowicz (Termedia Publishing House, 2011)
tissue disease. The main symptoms are atrophy and fibrosis of the connectivetissue stroma, preceded by changes in the small blood vessels.Pathogenesis of morphea is still unknown. The possible role of geneticfactors, immunological abnormalities, especially in cell-mediatedimmunity, trauma, viruses or infection with Borrelia burgdorferi is suspected.Several types of localized scleroderma can be distinguished: plaque morphea, generalized morphea, bullous morphea, linear morphea(scleroderma) and deep morphea.Objective. To present two cases of bullous morphea and therapeuticdifficulties connected with this disease.Case report. Two cases of bullous morphea are presented in 70- and 84-year-old women. Each of them was treated with individually chosentherapy. Initially they were treated with crystalline penicillin, hydrocortisone,vascular drugs; and UVA phototherapy. Afterwards, thepatients were treated with pulses of methylprednisolone andmethotrexate. The treatment led to suppression of the disease - blistershealed and the indurations diminished.Conclusions. The treatment of localized scleroderma is not satisfactory.It causes difficulties due to limited effectiveness of applied drugsand their side effects. It is crucial to start treatment as early as possible,when the pathological changes are in the initial stage.